Pendampingan Identifikasi Potensi Pengembangan Agrowisata Berbasis Partisipasi Masyarakat di Desa Tirtomulyo, Kretek, Bantul, Yogyakarta - Siti Nurul Rofiqo Irwan; Hani Perwitasari; Muhamad Muhamad (Institut Pertanian Bogor, 2021)
Tirtomulyo Village is located enroute the Parangtritis Beach, which is one of the main tourist destinations in the Bantul Region of Yogyakarta. This village has the potential to develop into an agro-tourism area based on the natural resources and community participation. Presently, community-based agro-tourism is being developed in this area through the Gadjah Mada University Assisted Village program. Therefore, this programme aims to 1) Identify the potential of natural resources and village landscapes; 2) Increase community participation in developing villages; and 3) Empower natural resources and village communities for agro-tourism development. Data were obtained from community participation-based agro-tourism planning using the Business Model Canvas (BMC) method and the Training on Trainer system from June to October 2020. Furthermore, during the Covid 19 pandemic, tourism education was carried out using an online method such as Google meet and whatsapp group platforms. The implementation of the direct meeting program (offline) was limited due to health protocol. Potential identification carried out by the community in 15 hamlets of Tirtomulyo Village shows the potential for natural resource attractions based on local wisdom consisting of natural resources, yards (pekarangan), cultural table 1dance, handicrafts, culinary, and fisheries. The result showed that online and offline discussions and the making of BMC posters are some of the efforts used in building villages for agro-tourism development. Furthermore, various natural resources as the potential of agro-tourism attractions have started to be empowered, including plant nurseries in the yard (pekarangan), peanut brittle, gula semut, and banana weevil chips well as a homestay. Therefore, the coordination of the inter-hamlet agro-tourism program at the village level still needs to be improved.